A nonanucleotide sequence involved in promotion of ribosomal RNA synthesis and RNA priming of DNA replication in yeast mitochondria. - Osinga, K A (1982)
We have examined the initiation of transcription of the mitochondrial genes for ribosomal RNA (rRNA) in the yeast Kluyveromyces lactis and show that these are transcribed independently from individual promoters. The mature large rRNA contains a 5' di- or triphosphate end which can be labelled in vitro with [alpha-32P]GTP using guanylyltransferase and this enabled us to determine the nucleotide sequence of its 5' terminus. For the small rRNA, a minor in vitro capped RNA species hybridizes in the region where--as judged from S1 nuclease protection experiments--the precursor of this RNA starts. We have determined the DNA sequence around the beginning of both rRNA genes and this reveals the existence of an identical nonanucleotide sequence (5' -ATATAAGTA- 3') just preceding the positions where the rRNAs start. This sequence is identical to the one preceding the rRNA genes in the mtDNA of the distantly related yeast Saccharomyces cerevisiae (Osinga, K.A. and Tabak, H.F. (1982) Nucl.Acids Res. 10, 3617-3626) and supports our proposal that this sequence motif is part of a yeast mitochondrial promoter. We have noticed that the same sequence is located in the putative origin of replication present in hypersuppressive petite mutants of S. cerevisiae and consider the possibility that this sequence is involved in RNA priming of DNA replication.